AGRISOFT to boost production for farmers and breeders - UMP, PNC (2020)
Concern with problems often faced by farmers or breeders in monitoring and regulating their crops or livestock has motivated a Universiti Malaysia Pahang (UMP) researcher to come up with a system called IoT-Enabled Farmer Digital Expert System @ AGRISOFT.